Herbs as a feed additive in the broilers for the sustainability of local products - Widodo, Wahyu; Sutanto, Adi; Dwi Rahayu, Imbang; Devi Anggraini, Aprilliana; Handayani, Trisakti; Hendroko Setyobudi, Roy; Mel, Maizirwan; Ngoc Huu, Nguyen (EDP Sciences, 2023)
The purpose was to determine the comparison of giving herbal herbs through feed and drinking water to the productivities of broilers. The research took place in the Closed House Cage and Animal Science Laboratory, Faculty of Agriculture and Animal Science, University of Muhammadiyah Malang, East Java, Indonesia. The material was Day Old Chick (DOC) broilers by number 200 and herbs in feed and drinking water. The treatment of herbs was divided into two types as follows: Herbs in feed (TA) and herbs in drinking water (TB). Then, herbs in the feed and drinking water were divided into four treatments as follows: T0: Feed without herbs or 0 % (as control), T1: Feed with herbs 1 %, T2: Feed with herbs 2 %, and T3: Feed with herbs 3 %, with five replications. The herbs used are mixed with several medicinal plants. The variables were body weight gain, final body weight, daily feed consumption, and feed conversion ratio. The research data were analyzed by quantitative descriptive analysis. The conclusion was giving herbs through feed was better in final body weight, body weight gain, and feed conversion ratio.